1996
DOI: 10.1063/1.115640
|View full text |Cite
|
Sign up to set email alerts
|

Deep level transient spectroscopic and Hall effect investigation of the position of the vanadium acceptor level in 4H and 6H SiC

Abstract: Hall effect, deep level transient spectroscopy (DLTS) and optical absorption measurements were employed in concert to determine the position of the vanadium acceptor level in vanadium and nitrogen doped 6H and 4H SiC. Hall effect results indicate that the acceptor position in 4H SiC is at 0.80 eV beneath the conduction band edge, and 0.66 eV for the 6H polytype. The DLTS signature of the defect in the 4H polytype showed an ionization energy of 0.80 eV and a capture cross section of 1.8×10−16 cm−2. The optical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(40 citation statements)
references
References 0 publications
2
29
1
Order By: Relevance
“…Initially, Cr and V were considered strong candidates for the origin of these levels as they have been reported at 0.74 and 0.80 eV below E c , respectively, and also have displayed high thermal stability as the incorporation of the impurity takes place either during the sublimation growth 3 or through ion implantation and postannealing at temperatures above 1300°C. 7 SIMS analysis coupled with the electrical depth profiling reveals that there is insufficient Cr in our samples to account for this level, which reaches concentrations у2 ϫ10 14 cm Ϫ3 after annealing of samples irradiated with electron doses у1ϫ10 15 cm Ϫ2 .…”
Section: Resulsts and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, Cr and V were considered strong candidates for the origin of these levels as they have been reported at 0.74 and 0.80 eV below E c , respectively, and also have displayed high thermal stability as the incorporation of the impurity takes place either during the sublimation growth 3 or through ion implantation and postannealing at temperatures above 1300°C. 7 SIMS analysis coupled with the electrical depth profiling reveals that there is insufficient Cr in our samples to account for this level, which reaches concentrations у2 ϫ10 14 cm Ϫ3 after annealing of samples irradiated with electron doses у1ϫ10 15 cm Ϫ2 .…”
Section: Resulsts and Discussionmentioning
confidence: 99%
“…Identification of these low concentration impurities and their associated positions in the electronic band gap can be complicated by the high doping concentrations (у10 18 cm Ϫ3 ) typically found in bulk samples which make the formation of either a p-n or Schottky-type diode difficult. Recently, Jenny et al 3,4 have reported the position of the vanadium acceptor level at E c Ϫ0.80 eV through the incorporation of the metallic impurity during sublimation growth while Achtziger et al have reported on the Cr level at E c Ϫ0.74 eV through the use of ion-implanted radioactive isotopes. 7 The identification and characterization of intrinsic defects, however, have received less attention.…”
Section: Introductionmentioning
confidence: 99%
“…When acting as a deep acceptor, vanadium forms a level at an energy 0.8 -1.0 eV below the conduction band, with the exact energy depending on the polytype (Jenny et al 1996), and compensates the shallow donors introduced by impurities from the growth process (Schneider et al 1990). The dominant vanadium donor state has been attributed to a level at 1.6 -1.7 eV below the conduction band (Mitchel et al 1999).…”
Section: Sic Materials Propertiesmentioning
confidence: 99%
“…[3][4][5][6][7][8] Photo-ESR spectroscopy indicated that the vanadium donor level is located at E v + 1.6 eV in 6H-SiC. 3 Evwaraye and co-workers conducted OAS measurements below room temperature and reported vanadium donor levels at E v + 1.73 eV and E v + 1.55 eV in n-type 4H-SiC and p-type 6H-SiC, respectively.…”
Section: Introductionmentioning
confidence: 95%
“…7 Jenny and co-workers attribute the activation energy of 0.66 eV deduced from the temperature-dependent Hall resistivity to the V 3+/4+ level in 6H-SiC and reported the acceptor position to be 0.80 eV below the conduction band edge in 4H-SiC. 8 As stated earlier, calculations predict that vanadium complexes will also produce levels within the bandgap of 4H SiC. Evwaraye and co-workers reported that peaks at 1.17 eV in 4H-SIC and 1.13 eV in 6H-SiC are most likely a vanadium complex.…”
Section: Introductionmentioning
confidence: 97%